Revitalisasi Peran Keluarga dan Masyarakat dalam Menanggulangi Krisis Kesehatan Mental: Pendekatan Integratif Berbasis Nilai-Nilai Islam dan Komunitas Sosial Modern - Muhammad Alfian (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
The mental health crisis in Indonesia is increasingly alarming, exacerbated by the COVID-19 pandemic, social stigma, and unequal access to professional services. A clinical approach alone is not enough to address this complex problem. This study offers a novelty in the form of an integrative approach: revitalizing the role of families and communities based on Islamic values (rahmah, ta'awun, shabr, syura, tarbiyah ruhiyah) combined with the use of digital social communities as a medium for education, discussion, and support systems. The research method used is a literature study with a descriptive qualitative approach, reviewing national and international literature, social support theory (Cohen & Wills, 1985), religious coping (Koenig, 2012), and Bronfenbrenner's ecological theory (1979). The results of the study show that families play a strategic role in the prevention, assistance, and referral of mental health cases, while digital communities are effective as spaces for education and emotional validation, with scalability and anonymity as their main strengths. Concrete strategies offered include family education, stigma-free campaigns on social media, spiritual care hotlines, and cross-sector collaboration. This approach is in line with the collectivist culture of Indonesian Muslim society and is more adaptive in the digital era. This research is expected to serve as a conceptual foundation for practical programs, public policy, and further research to create a more caring, stigma-free, and resilient society in the face of mental health crises.